STUDI LITERATUR PENGARUH MEDIA PEMBELAJARAN BERBASIS MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR PESERTA DIDIK PADA PELAJARAN IPA DI SEKOLAH DASAR - Barokah , Awalina; Syifa Fauziah, Annisa; Rachmadini , Eris Fadila; Aprilia , Amanda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Science learning in elementary schools is a learning activities that approach the natural environment or natural phenomena of daily life involving the senses, and the use of audiovisual media is very supportive in the science learning process. This research aims to determine the effect of audio-visual based learning media on science learning subjects in elementary schools. The benefit is to help students understand the applied science learning material. The method used is the literature study research method, literature study is a method produced from reading sources which produces accurate data. Learning outcomes obtained from the use of audio-visual media in science learning.